Genome evaluation of banana cultivars based on morphological character and Inter-Simple Sequence Repeat (ISSR) molecular marker - Didik Wahyudi; Uslan; KHAFIDHOTUR RIFLIYAH (Society for Indonesian Biodiversity, 2020)
Abstract. Wahyudi D, Rifliyah K, Uslan. 2020. Genome evaluation of banana cultivars based on morphological character and Inter-Simple Sequence Repeat (ISSR) molecular marker. Biodiversitas 21: 2982-2990. This study aims to evaluate the genome group and to investigate the genetic variability of banana cultivar using morphological character and ISSR molecular marker. Fourteen banana cultivars with genomic group AA, AAA, AAB, ABB, and BB was used. All samples were Identified morphologically based on minimal descriptors for bananas issued by the International Plant Genetic Resources Institute (IPGRI). Total genomic DNA was extracted using DNA Isolation Kit Promega Wizard®. ISSR primer was used in this study, including UBC834, UBC835, UBC843, UBC848, and UBC855. Clustering analysis was used to evaluate genome grouping of the banana cultivar. Clustering analysis of morphological character was performed using the unweighted pair group method with arithmetic mean (UPGMA) algorithm and Bray-Curtis coefficient similarity using Paleontological Statistics (PAST) software. Morphological and ISSR was successfully differentiate banana cultivars and relatively similar to previous genome grouping. However, pisang Triolin (AAB) must be evaluated since it belongs to AAA group. The identification of cultivars and classification of their genome groups based on morphological characteristics and proved by molecular markers will strengthen the establishment of Musa improvement strategy especially in Indonesia and ease the breeder to identify desirable traits of progenitor to be included in the breeding program.